2012
DOI: 10.1097/aog.0b013e31823d4167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Text Messages on Oral Contraceptive Continuation

Abstract: ClinicalTrials.gov, www.ClinicalTrials.gov, NCT00677703.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
151
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 14 publications
6
151
2
4
Order By: Relevance
“…Indeed, in our larger randomized controlled trial, women who received our comprehensive daily text message intervention (which entailed educational information and behavioral reminders) were 44% more likely to continue OCs at 6 months compared with the control group. 11 Unfortunately, we had limited power to further examine the effect of each OC knowledge dimension, as well the effect of ''dosage'' of intervention content for each dimension, on OC continuation and pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in our larger randomized controlled trial, women who received our comprehensive daily text message intervention (which entailed educational information and behavioral reminders) were 44% more likely to continue OCs at 6 months compared with the control group. 11 Unfortunately, we had limited power to further examine the effect of each OC knowledge dimension, as well the effect of ''dosage'' of intervention content for each dimension, on OC continuation and pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Potential covariates, including sociodemographic and reproductive correlates we had previously shown to be associated with OC knowledge and continuation, were considered for inclusion in regression models if their p-value in bivariate tests was £ 0.25. 11,12 We present final reduced multivariable models in which we retained only those covariates that were associated with OC knowledge or continuation at p < 0.05. For variables that appeared to be collinear (e.g., age and grade of education), we retained those variables with the strongest effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Castaño et al found that daily text-message reminders that included an educational message significantly decreased the proportion of OCP users who experienced an extended 7-day gap in use during the study. 31 Conversely, using electronic monitoring devices to record adherence, Hou et al found no difference in adherence between those receiving daily text reminders (minus the educational component) and the control group. 32 The majority of participants receiving reminders found them to be acceptable and useful.…”
Section: Remindersmentioning
confidence: 99%
“…This is also the age group that often selects an OC as their form of contraception (39) . Unfortunately, OC discontinuation is high (55)(56)(57) , often occurs without consulting a physician (45) and leaves women at risk for an unintended pregnancy. Therefore, attaining adequate folate stores in this population is very important.…”
Section: Discussionmentioning
confidence: 99%